Design and fabricate remote controlled submarine with on board wireless camera - Zulkiplie, Jamal (2007)
Nowadays, submarine can be use in many fields including research. For current practice, RC (radio control) submarine can be used to do underwater monitoring. Current RC submarine are expensive, and new design in this project are used to build a local RC submarine with on board wireless camera. In this project,the cost will be optimum and using an easy to obtain parts. The main things in the RC submarine are controller system and watertight. Research and comparison are done to make sure the flow of the project run smoothly. The fabrication phase started with making a control system for the submarine. A controller circuit consists of two important components; relays and radio control receiver. This will control pumps and motor. The ballast tank is made from PVC (poly vinyl chloride) pipes, sockets and round shape Perspex. To make a control system for the ballast system is the tough challenge in this project. The circuit is sensitive and easy to malfunctions. To make the tank watertight, silicon adhesive applied to avoid from water to fill the dry compartment of the ballast tank. For the result, the ballast system is finish after designing and fabricating process. Despite of that, the ballast system operated not fully functionally. The controller system had some problem and only one of the pump run.